Cupang Halfmoon sebagai Inspirasi Penciptaan Feminine Romantic Style - Fadhila Febriani; Novina Yeni Fatrina; Nofi Rahmanita; Fendi Nofrian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This work is entitled "Halfmoon Betta as an Inspiration for Feminine Romantic Style Fashion" which is inspired by the halfmoon betta in the form of feminine clothing. The creation of this final project aims to create a feminine romantic style fashion with the source of the halfmoon betta. The beauty of the fin shape and the variety of pastel colors in the halfmoon betta are used as inspiration in processing the design, silhouette, decorative details, and color selection of the clothing. The creation method is carried out through several stages, namely exploration of the source of ideas, design planning, material selection, and the process of changing the clothing. In the creation process, the artist applies decorative techniques in the form of ruffles, borders, sequin embroidery, and the use of lace to strengthen the character of the feminine romantic style. The material used is a typical Jepara baron woven fabric that has a texture in the form of fish scales so that it supports the concept of creation. The colors used consist of light purple, light blue, light pink, and Broken White. The results of the creation are three levels of clothing, namely ready to wear, ready to wear deluxe, and haute couture. This creation is expected to be an innovation in the development of romantic feminine fashion, utilizing the visual beauty of the halfmoon betta as a source of inspiration for fashion creations.